CONSIDERATIONS OF MULTI-IMAGING MODALITIES FOR DIAGNOSING OF SIALOLITHIASIS IN THE SUBMANDIBULAR GLAND: A CASE REPORT - Norlaila Sarifah; Fadhlil Ulum A. Rahman; Aga Satria Nurrachman; Azhari Azhari; Lusi Epsilawati (FKG Unlam, 2022)
Introduction: Sialolithiasis is a condition that occurs due to obstruction in the salivary gland or ductus excretory by calculus or sialolith. Sialolithiasis was the most common disease of salivary glands with a percentage of about 50%, and approximately 80-90% occurs in the submandibular gland. This paper analyzes the sialolithiasis in the submandibular gland being reviewed from the radiograph. Radiography screening becomes one of the most essential supporting examinations to help enforce the diagnosis and treatment plan to be conducted.Case : A 33-year-old patient was seen in Oral and Maxillofacial Surgery of General Hospital, Bandung, Indonesia. The chief complaint of swelling in the right side of his lower jaw was under the chin. Multi-imaging and radiography modalities screening were panoramic, occlusal, cervical, CT Scan, USG, and sialography. Case management : On radiographic examination, radiological suspicion was sialolithiasis with a well-defined and irregularly shaped radiopaque lesion in the lower right jaw area. Therefore, radiographic techniques with different modalities were performed to support each other in delivering accurate radiodiagnosis. Conclusion: The considerations of using appropriate multi-imaging and radiographic modalities are necessary to confirm the diagnosis of sialolithiasis in the submandibular salivary glands, especially in hard-recognized cases on plain radiographs. Keywords: Radiography, Sialolithiasis, Submandibular gland